2020
DOI: 10.33545/pathol.2020.v3.i3a.258
|View full text |Cite
|
Sign up to set email alerts
|

Study on the patterns of semen analysis in infertile males at a tertiary setup in Devanahalli

Abstract: Background: Infertility is a stigma in our social environment where 40-50% is due to male infertility. Aim: To evaluate the different patterns of semen abnormalities seen with associated factors. Methods: A prospective study was carried out at the Pathology Laboratory on seminal fluid with male factor as the cause for infertility. Semen samples were analyzed by manual method, using WHO guidelines. Result: Out of 110 samples studied, 74 were Normozoospermia with normal semen parameters and 36 had abnormal semen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…Physical obstruction and retrograde ejaculation may also contribute to low ejaculated volume. Anuja et al 17 reported 6% oligospermia which was comparable to our study, while Fouzia et al reported 5 (11.11%) same as 13.3% by Chituri et al 16 A very high percentage of oligospermia as 39.7% is reported by Aulia et al from Jakarta may be for the same reason as they reported higher percentage of azoospermia. 6 Mean ejaculated volume in normopspermia was 3.25 ± 1.35 vs 2.05 ± 2 in oligospermia and 2.43 ± 1.19 in azoospermia sample respectively.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Physical obstruction and retrograde ejaculation may also contribute to low ejaculated volume. Anuja et al 17 reported 6% oligospermia which was comparable to our study, while Fouzia et al reported 5 (11.11%) same as 13.3% by Chituri et al 16 A very high percentage of oligospermia as 39.7% is reported by Aulia et al from Jakarta may be for the same reason as they reported higher percentage of azoospermia. 6 Mean ejaculated volume in normopspermia was 3.25 ± 1.35 vs 2.05 ± 2 in oligospermia and 2.43 ± 1.19 in azoospermia sample respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Majority of our patients had normal semen volume 97.84%, while 1.6% showed hypospermia (<1.5ml), and hyperspermia in 0.5%. These results were comparable to a study conducted in Delhi, 10 and Dewanhalli, 17 which revealed 91% and 92% normal semen volume, while 4.9% and 7% having hypospermia (less than 1.5ml) respectively. Similar results are also shown by Fauzia et al 5 The adequacy of semen volume in our study could be the result of sexual abstinence of 3-4 days.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation